118k views
6 votes
Someone help pls asap

Someone help pls asap-example-1

2 Answers

10 votes

Answer:


→(g - f)(x) = g(x) - f(x) \\ → (log(x - 3) + 6) - (\sqrt[3]{12x + 1} + 4) \\→ log(x - 3) + 6 - \sqrt[3]{12x + 1} - 4 \\→\boxed{ log(x - 3) - \sqrt[3]{12x + 1} + 2}✓

D. is the right answer.

User Travis Brown
by
5.6k points
9 votes

Answer:


(g - f)(x) = log(x-3)- \sqrt[3]{12x +1} + 2

Explanation:

Given


f(x) = \sqrt[3]{12x +1} + 4


g(x) = log(x-3)+6

Required

Determine (g - f)(x)

In functions:


(g - f)(x) = g(x) - f(x)

So, we have:


(g - f)(x) = log(x-3)+6 - (\sqrt[3]{12x +1} + 4)

Open bracket


(g - f)(x) = log(x-3)+6 - \sqrt[3]{12x +1} - 4

Collect Like Terms


(g - f)(x) = log(x-3)- \sqrt[3]{12x +1} - 4+6


(g - f)(x) = log(x-3)- \sqrt[3]{12x +1} + 2

User Mcmil
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.